2012
DOI: 10.1007/s10562-012-0820-6
|View full text |Cite
|
Sign up to set email alerts
|

Steam Reforming on Transition-Metal Carbides from Density-Functional Theory

Abstract: A screening study of the steam reforming reaction on clean and oxygen covered early transitionmetal carbides surfaces is performed by means of density-functional theory calculations. It is found that carbides provide a wide spectrum of reactivities, from too reactive via suitable to too inert. Several molybdenum-based systems are identified as possible steam reforming catalysts. The findings suggest that carbides provide a playground for reactivity tuning, comparable to the one for pure metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…These results suggest that the most relevant Mo 2 C(001) surface to use for studying syngas reactions is the oxygen passivated surface or hydrocarbon terminated surface. Previous work has suggested that the oxygen passivated surface may temper the high reactivity of the Mo-terminated Mo 2 C(001) surface, leading to improved catalytic activity [52]. Adsorbed oxygen, carbon, or hydrocarbons can desorb as part of catalytic cycles, therefore the termination will depend on both thermodynamic conditions and reaction kinetics.…”
Section: Ch X and Oh X Coveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the most relevant Mo 2 C(001) surface to use for studying syngas reactions is the oxygen passivated surface or hydrocarbon terminated surface. Previous work has suggested that the oxygen passivated surface may temper the high reactivity of the Mo-terminated Mo 2 C(001) surface, leading to improved catalytic activity [52]. Adsorbed oxygen, carbon, or hydrocarbons can desorb as part of catalytic cycles, therefore the termination will depend on both thermodynamic conditions and reaction kinetics.…”
Section: Ch X and Oh X Coveragesmentioning
confidence: 99%
“…In order to further improve the performance of molybdenum carbide catalysts it is of value to understand the reactivity, selectivity, and stability of molybdenum carbide under various conditions. Numerous theoretical studies have investigated the surface stability [38,39,40,41], adsorption energies [42,43,44,45,46,47,48,49,50,51,40,52], reaction energetics [53,54,46,55,52], and alkali-doping [40,50] on Mo 2 C. The most well-studied surface is the Mo 2 C(001) surface, and both orthorhombic and hexagonal close packed Mo 2 C have been investigated. The results have indicated that the non-polar (011) surface is the most stable regardless of carbon chemical potential, but that the surface energies are sufficiently close that all surfaces are expected to be present on nanoparticles [40,39].…”
Section: Introductionmentioning
confidence: 99%
“…27,[32][33][34][35] Recently, Medford et al applied ab initio thermodynamics and DFT to study the stability of surface structures of Mo 2 C and adsorption of reactive intermediates as well as C-O bond dissociation on the Mo 2 C surface. 36 Pistonesi et al studied adsorption of alkali metal on Mo 2 C surfaces and its effect on CO adsorption and dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure c presents the (111) facet, which has Mo‐terminated or C‐terminated surface. It has been reported that the MoC (111) surface has a higher reactivity in the catalyzed reduction than the MoC (100) surface, which, however, makes the (111) surface easily oxidized . We calculated the surface energy of these surfaces (see details in the Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
“…Different surfaces of carbides also possess different electrochemical properties. The Mo‐terminated or C‐terminated fcc MoC (111) surface is easily oxidized though it has higher reactivity compared to fcc MoC (100) surface …”
Section: Introductionmentioning
confidence: 99%